Parametric study of orthopedic insole of valgus foot on partial foot amputation. Issue 8 (10th June 2016) - Guo, Jun-Chao; Wang, Li-zhen; Chen, Wei; Du, Cheng-Fei; Mo, Zhong-Jun; Fan, Yu-Bo
Abstract: Orthopedic insole was important for partial foot amputation (PFA) to achieve foot balance and avoid foot deformity. The inapposite insole orthosis was thought to be one of the risk factors of reamputation for foot valgus patient, but biomechanical effects of internal tissues on valgus foot had not been clearly addressed. In this study, plantar pressure on heel and metatarsal regions of PFA was measured using F-Scan. The three-dimensional finite element (FE) model of partial foot evaluated different medial wedge angles (MWAs) (0.0°–10.0°) of orthopedic insole on valgus foot. The effect of orthopedic insole on the internal bone stress, the medial ligament tension of ankle, plantar fascia tension, and plantar pressure was investigated. Plantar pressure on medial heel region was about 2.5 times higher than that of lateral region based on the F-Scan measurements. FE-predicted results showed that the tension of medial ankle ligaments was the lowest, and the plantar pressure was redistributed around the heel, the first metatarsal, and the lateral longitudinal arch regions when MWA of orthopedic insole ranged from 7.5° to 8.0°. The plantar fascias maintained about 3.5% of the total load bearing on foot. However, the internal stresses from foot bones increased. The simulation in this study would provide the suggestion of guiding optimal design of orthopedic insole and therapeutic planning to pedorthist.